2020
DOI: 10.1093/ckj/sfaa057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of enoxaparin in preventing coagulation during high-flux haemodialysis, expanded haemodialysis and haemodiafiltration

Abstract: Background Low-molecular-weight heparins (LMWHs) are easily dialysable with high-flow membranes; however, it is not clear whether the LMWH dose should be adjusted according to the membrane type and dialysis technique. This study aimed to evaluate the influence of the dialyser on anticoagulation of the extracorporeal dialysis circuit. Methods Thirteen patients received the same dose of LMWH through the arterial port via three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…The delay in LMWH reaching the dialyzer when applied through venous port, with decrease in enoxaparin blood concentration, leads to its anticoagulation effect before reaching the membrane and to a less‐efficient enoxaparin removal than that through the arterial port. In fact, when enoxaparin was administered through the arterial line in similar circumstances, significant differences were found in postdialysis aXa [26], supporting our hypothesis. Earlier study found differences in aXa comparing two different dialyzers in HDF, with enoxaparin applied through the venous port [20].…”
Section: Discussionsupporting
confidence: 75%
“…The delay in LMWH reaching the dialyzer when applied through venous port, with decrease in enoxaparin blood concentration, leads to its anticoagulation effect before reaching the membrane and to a less‐efficient enoxaparin removal than that through the arterial port. In fact, when enoxaparin was administered through the arterial line in similar circumstances, significant differences were found in postdialysis aXa [26], supporting our hypothesis. Earlier study found differences in aXa comparing two different dialyzers in HDF, with enoxaparin applied through the venous port [20].…”
Section: Discussionsupporting
confidence: 75%
“…This may result from higher LMWH removal, although it has been hypothesized that a high ultrafiltration volume applied during OL‐HDF may increase procoagulatory activity via shear stress and decrease of aXa activity levels through enoxaparin consumption 22 . In MCO‐HD, a trend towards lower post‐dialysis aXa levels compared to HF‐HD has also been reported when enoxaparin 40 mg was administered through the arterial blood line 5 min after the start of dialysis 20 . Besides removal or consumption of LMWH, other mechanisms may be involved in the decrease of aXa activity after dialysis sessions.…”
Section: Discussionmentioning
confidence: 99%
“…22 In MCO-HD, a trend towards lower post-dialysis aXa levels compared to HF-HD has also been reported when enoxaparin 40 mg was administered through the arterial blood line 5 min after the start of dialysis. 20 Besides removal or consumption of LMWH, other mechanisms may be involved in the decrease of aXa activity after dialysis sessions. Indeed, since LMWH are negatively charged, adsorption-binding and clearance rate may vary, depending on the surface roughness and electrical charge of dialysis membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HDF as compared to HD removes larger molecules to a greater extent due to use of convection as compared to diffusion, which may also explain the difference in nadroparin clearance between these types of hemodialysis [6,30,31]. Some studies reported a significantly lower anti-Xa level in HDF versus high-flux hemodialysis (HF-HD), indicating a higher nadroparin clearance in HDF versus HF-HD [32,33]. However, Sridharan et al reported no difference in required LMWH dose to achieve adequate anti-Xa levels between HDF and HF-HD, suggesting no effect of dialysis mode on nadroparin clearance [34].…”
Section: Discussionmentioning
confidence: 99%